Long-term results of allogeneic stem cell transplantation in adult pH- negative high-risk acute lymphoblastic leukemia - Beelen, Dietrich W.; Arnold, Renate; Stelljes, Matthias; Alakel, Nael; Brecht, Arne Jörn; Bug, Gesine; Bunjes, Donald; Faul, Christoph; Finke, Jürgen; Franke, Georg-Nikolaus; Holler, Ernst; Kobbe, Guido; et al. (Transplantation and cellular therapy, 2022)
Allogeneic hematopoietic stem cell transplantation (HCT) is standard treatment for adult high-risk (HR) acute lymphoblastic leukemia (ALL) and contributed to the overall improved outcome. We report a consecutive cohort of prospectively defined HR patients treated on German Multicenter Acute Lymphoblastic Leukemia trials 06/99-07/03 with similar induction/consolidation therapy and HCT in first remission. A total of 542 patients (15-55 years) with BCR-ABL-negative ALL were analyzed. Sixty-seven percent received HCT from matched unrelated donors (MUD) and 32% from matched sibling donors (MSD). The incidence of non-relapse mortality (NRM) was 20% at 5 years. NRM occurred after median 6.6 months; the leading cause (46%) was infection. NRM after MUD decreased from 39% in trial 06/99 to 16% in trial 07/03 (P < .00001). Patient age was the strongest predictor of NRM. The 5-year relapse incidence was 23% using MSD and 25% using MUD. Minimal residual disease (MRD) was the strongest predictor of relapse (45% for molecular failure versus 6% for molecular CR; P < .0001). The median follow-up was 67 months, and the 5-year survival rate was 58%. Age, subtype/high risk feature, MRD status, trial and acute GvHD were significant prognostic factors. We provide a large reference analysis with long follow-up confirming a similar outcome of MSD and MUD HCT and improved NRM for MUD HCT over years. MRD has a strong impact on relapse risk, whereas age was the strongest predictor of NRM. New adapted conditioning strategies should be considered for older patients combined with the goal to reduce the MRD level before stem cell transplantation.